The Role of NU Figures in Cultural Da‘wah: A Collaborative Study of K.H. Abdul Manan Dipomenggolo and Mbah Ketok Jenggot in Tremas - Afra Sabrina Mumtaz; Fadhilah Nur Ramadhani Yumna; Munirotuz Zahro Wardati; Mohammad Fajriyanto; Muhammad Rizal Kurniawan (Lakpesdam PCNU Kota Salatiga, 2025)
Cultural da‘wah in Java has frequently advanced through negotiated encounters between Islamic teachings and local socio-cultural systems. In Tremas (Pacitan), the historical narratives of land clearing (babat alas) and the subsequent emergence of pesantren leadership illustrate how spiritual authority and social legitimacy can jointly shape community Islamization across different periods. This study addresses two questions: (1) How does cultural da‘wah through acculturation, indigenization, and cultural mediation explain the roles and legitimacy of local figures (Mbah Ketok Jenggot and K.H. Abdul Manan Dipomenggolo) in fostering the acceptance of Islam in Tremas? (2) How does the pesantren as an educational da‘wah institution—via religious habitus formation, cadre reproduction, and scholarly networks explain K.H. Abdul Manan’s strategies in institutionalizing Islam sustainably in Tremas? Employing a qualitative descriptive design, the study draws on documentary data from Manuskrip Tremas (Ahmad Muhammad) and semi-structured interviews with key local custodians (the hamlet head and the site caretaker). Data were collected through systematic reading–note-taking and interviews, then analyzed using an interactive model (data reduction, display, and conclusion drawing). The findings indicate that Mbah Ketok Jenggot functions as a cultural mediator whose land-clearing narratives and symbolic authority provide early socio-cultural legitimacy, enabling Islam to enter local meaning systems gradually. K.H. Abdul Manan’s da‘wah is consolidated through the establishment of mosque-based learning and pesantren infrastructure that stabilizes religious practice, produces disciplined religious habitus, and sustains transmission through educational routines and expanding scholarly lineages. The study recommends strengthening local historical-literacy documentation as a cultural da‘wah resource, structuring pesantren-based cadre formation for continuity, and expanding inter-pesantren/NU networks for broader educational impact. Future research should deepen triangulation across archives, multi-informant narratives, and long-term ethnographic observation to refine understanding of cultural mediation processes.